A new species of Coleodactylus Parker, 1926 (Squamata: Sphaerodactylidae) from the Atlantic Forest of northeast Brazil - Gonçalves, Ubiratan; Torquato, Selma; Skuk, Gabriel; de Araújo Sena, George (Zootaxa, 2012)
A new species, Coleodactylus elizae sp. nov., is described for the Atlantic Forest of Northeastern Brazil. It is distinguishedfrom other Coleodactylus species by the following character combinations: one nearly completely divided or two rostralscales, dorsal scales smooth and four scales forming the ungual sheath. The color pattern consists of white spots distributed over a pinkish background. Coleodactylus elizae sp. nov. is a forest species inhabiting bromeliads.